Benchmarking selective capture of trace CO2 from C2H2 using an amine-functionalized adsorbent - Jin-Sheng Zou; Zhi-Peng Wang; Yassin H. Andaloussi; Jiapeng Xue; Wanli Zhang; Bryan E. G. Lucier; Zeyang Zhang; Yanan Jia; Xue-Cui Wu; Jiahan Li; Yining Huang; Michael J. Zaworotko; et al. (Nature Communications)
Abstract Purifying C2H2 by removing trace CO2 is critically needed yet challenged by their analogous physical properties. Herein, we report a commercial resin adsorbent HP20 (Diaion® HP-20 Resin) loaded with polyethyleneimine (PEI@HP20) which selectively captures trace CO2 and excludes C2H2. PEI@HP20 possesses a high CO2 adsorption capacity (4.35 mmol/g) at 100 kPa and 298 K and a record CO2/C2H2 uptake ratio compared with all reported CO2-selective adsorbents. The ideal adsorbed solution theory selectivity reaches 1.33×107. The pilot-scale pressure-temperature swing adsorption on 2 kg PEI@HP20 further validated that it can obtain >99.99% purity C2H2 from CO2/C2H2(1/99, v/v) mixtures with a high yield of 344.7 g per cycle. The combination of multinuclear solid-state Nuclear Magnetic Resonance, Fourier Transform infrared spectroscopy and density functional theory calculations reveal that the performance of PEI@HP20 relies on a dual chemisorption/physisorption mechanism. This work highlights a promising method to develop green, low cost, high efficiency, and readily scalable CO2-selective adsorbent.